2017
DOI: 10.1016/j.jhealeco.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Retirement blues

Abstract: This paper analyses the short- and longer-term effects of retirement on mental health in ten European countries. It exploits thresholds created by state pension ages in an individual-fixed effects instrumental-variable set-up, borrowing intuitions from the regression-discontinuity design literature, to deal with endogeneity in retirement behaviour. The results display no short-term effects of retirement on mental health, but a large negative longer-term impact. This impact survives a battery of robustness test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 45 publications
2
55
1
Order By: Relevance
“…By exploiting the discontinuities in retirement behaviour across countries, they find significant evidence that retirement has a health-preserving effect on overall general health. Interestingly, Heller-Sahlgren [ 19 ] also using the SHARE dataset finds that retirement does not have any immediate significant negative effect on mental health, but that there is a significant negative effect in the long term. Several studies have found positive health effects of policy reforms that induce early retirement (Coe and Lindeboom [ 11 ], Bloemen et al [ 5 ], Hallberg et al [ 18 ]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By exploiting the discontinuities in retirement behaviour across countries, they find significant evidence that retirement has a health-preserving effect on overall general health. Interestingly, Heller-Sahlgren [ 19 ] also using the SHARE dataset finds that retirement does not have any immediate significant negative effect on mental health, but that there is a significant negative effect in the long term. Several studies have found positive health effects of policy reforms that induce early retirement (Coe and Lindeboom [ 11 ], Bloemen et al [ 5 ], Hallberg et al [ 18 ]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most frequently used instrument is age-specific retirement incentives, such as early retirement windows or eligibility age thresholds. This strategy has been used both in cross-country studies (e.g., Rohwedder et al 2010;Sahlgren 2012;Heller-Sahlgren 2017;Mazzona andPeracchi 2012, 2017;Coe and Zamarro 2011;Godard 2016) and in within-country studies (e.g., Charles 2004; Bound and Waidmann 2007;Neuman 2008;Bonsang et al 2012;Gorry et al 2015;Behncke 2012). The identifying assumption is that the instruments affect health only indirectly through their effects on the age of retirement.…”
Section: Previous Literaturementioning
confidence: 99%
“…The net effect of retirement on mental health is also difficult to predict. Retirement might have a positive impact on mental health through increased sleep duration (Eibich 2015;Vahtera et al 2009) and diminished work stress (Midanik et al 1995) but could also increase social isolation and depression (Börsch-Supan and Schuth 2014; Dave et al 2008;Heller-Sahlgren 2017). Even though these papers differ along several important dimensions, such as the population being studied, health outcomes and empirical methodology, these contrasting results are also likely to stem from the lack of convincing empirical strategies to deal with endogenous selection into retirement.…”
Section: Previous Literaturementioning
confidence: 99%
“…As such, they posited that retirement would contribute positively to mental health. Most studies have shown positive associations between retirement and mental health ( Airagnes et al, 2015 ; Butterworth et al, 2006 ; Drentea, 2002 ; Jokela et al, 2010 ; Mandal & Roe, 2008 ; Mänty et al, 2018 ; Mein, Martikainen, Hemingway, Stansfeld, & Marmot, 2003 ; Nuttman-Shwartz, 2004 ; Oksanen & Virtanen, 2012 ; Olesen, Rod, Madsen, Bonde, & Rugulies, 2015 ; Reitzes, Mutran, & Fernandez, 1996 ; Westerlund et al, 2010 ), but some have also found negative ( Dave, Rashad, & Spasojevic, 2008 ; Heller-Sahlgren, 2017 ; Hyde, Ferrie, Higgs, Mein, & Nazroo, 2004 ; Wheaton, 1990 ) or no associations at all ( Coe & Zamarro, 2011 ; Horner & Cullen, 2016 ; Laaksonen et al, 2012 ; Mojon-Azzi, Souza-Poza, & Widmer, 2007 ; Yeung, 2013 ). Retirement has also been associated with physical health functioning, physical (dis)abilities and (chronic) illnesses ( Gall, Evans, & Howard, 1997 ; Hessel, 2016 ; Seitsamo & Klockars, 1997 ; van Zon, Bültmann, Reijneveld, & de Leon, 2016 ), and self-rated general health ( Rijs, Cozijnsen, & Deeg, 2011 ; Seitsamo & Klockars, 1997 ; van den Bogaard, Henkens, & Kalmijn, 2016 ; van Solinge, 2007 ; Westerlund et al, 2009 ), with mixed evidence.…”
mentioning
confidence: 99%